2021
DOI: 10.3390/su131910802
|View full text |Cite
|
Sign up to set email alerts
|

The Mediated Moderating Role of Organizational Learning Culture in the Relationships among Authentic Leadership, Leader-Member Exchange, and Employees’ Innovative Behavior

Abstract: Previous studies have shown that enhancing employees’ innovative behavior can facilitate organizations’ sustainable competitiveness. This study investigated the relationship between authentic leadership and employees’ innovative behavior in Korean manufacturing and service companies. Moreover, the study examined the complex processes and conditions underlying this relationship. The results indicated that authentic leadership was significantly related to employees’ innovative behavior and that leader–member exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…While some of these business challenges have been discussed in the literature (see [95][96][97]), our analysis of the underpinning connotations of the textual data via concordance analysis (see Table 2) reveals an additional psychological meta-challenge that is interwoven with the business challenges (e.g., 'it's been pretty depressing thinking about how much income we've lost since March': ABC News, 05.05.2020). The situation has created uncertainty among business leaders and was described as creating a 'pressure cooker' (Gourmet Traveller, 03.04.2020) environment, causing stress.…”
Section: Challenges Facing Hospitality Business Leadersmentioning
confidence: 89%
“…While some of these business challenges have been discussed in the literature (see [95][96][97]), our analysis of the underpinning connotations of the textual data via concordance analysis (see Table 2) reveals an additional psychological meta-challenge that is interwoven with the business challenges (e.g., 'it's been pretty depressing thinking about how much income we've lost since March': ABC News, 05.05.2020). The situation has created uncertainty among business leaders and was described as creating a 'pressure cooker' (Gourmet Traveller, 03.04.2020) environment, causing stress.…”
Section: Challenges Facing Hospitality Business Leadersmentioning
confidence: 89%
“…Research has suggested that charismatic leadership has a positive impact on group innovation behavior. Charismatic leaders tend to create an environment that fosters creativity, risk-taking and innovation, which can lead to greater group innovation (Jung et al , 2021). Charismatic leaders are known to inspire and motivate their followers to think outside the box, take calculated risks and generate new ideas (Koh and Boo, 2001).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Despite having limited literature that examined the relationship between organizational learning culture and innovative work behavior, this result is aligned with many previous studies. It was discovered that organizational learning culture was positively associated with technical innovation in Spanish employees (Sanz-Valle et al, 2011), played a critical role as a mediator in company culture and organizational innovation relationship in Iranian companies (Abdi et al, 2018), as well as moderated the relationship between leader-member exchange and innovative behavior on manufacturing workers in Korea (Jung et al, 2021). Referring to the content analysis research conducted by Zennouche, Zhang, and Wang (2014) also included organizational culture as one of the influencing factors of innovation, which is consistent with the results of the current study.…”
Section: Hypothesis Testingmentioning
confidence: 99%